Where next with HDL assays?. Issue 4 (August 2018) - Niisuke, Katrin; Horvath, Katalin V.; Asztalos, Bela F.
Abstract : Purpose of review: The inverse association between HDL cholesterol (HDL-C) and cardiovascular disease (CVD) has been unequivocally proven in the past several decades. However, some interventions aiming to increase HDL-C failed to reduce CVD risk. HDL is structurally and functionally complex and HDL-associated metrics other than HDL-C, such as the concentration, composition, and functionality of HDL particles, have been considered as better determinants of CVD risk. A large body of recent research has addressed changes in HDL functions and HDL subpopulations in CVD with the goal of discovering novel and reliable biomarkers and targets for the treatment or prevention of CVD. Recent findings: We have reviewed recent findings on HDL composition, HDL particle concentrations, and cell-cholesterol efflux capacity that have lately contributed to our understanding of HDL's role in CVD. Summary: We point out that a major problem in HDL research is the lack of standardization of HDL assays that has led to discrepancies among studies. Therefore, there is a need for new standardized assays that capture the complexities of key HDL parameters.